Chiropractic Spinal Adjustment Increases the Cortical Drive to the Lower Limb Muscle in Chronic Stroke Patients - Navid, Muhammad Samran; Niazi, Imran Khan; Lelic, Dina; Amjad, Imran; Kumari, Nitika; Shafique, Muhammad; Holt, Kelly; Rashid, Usman; Drewes, Asbjørn Mohr; Haavik, Heidi (Frontiers in Neurology, 2022)
This study aimed to investigate the effects of a single session of chiropractic spinal adjustment on the cortical drive to the lower limb in chronic stroke patients. In a single-blinded, randomized controlled parallel design study, 29 individuals with chronic stroke and motor weakness in a lower limb were randomly divided to receive either chiropractic spinal adjustment or a passive movement control intervention. Before and immediately after the intervention, transcranial magnetic stimulation (TMS)-induced motor evoked potentials (MEPs) were recorded from the tibialis anterior (TA) muscle of the lower limb with the greatest degree of motor weakness. Differences in the averaged peak-peak MEP amplitude following interventions were calculated using a linear regression model. Chiropractic spinal adjustment elicited significantly larger MEP amplitude (pre = 0.24 ± 0.17 mV, post = 0.39 ± 0.23 mV, absolute difference = +0.15 mV, relative difference = +92%, p < 0.001) compared to the control intervention (pre = 0.15 ± 0.09 mV, post = 0.16 ± 0.09 mV). The results indicate that chiropractic spinal adjustment increases the corticomotor excitability of ankle dorsiflexor muscles in people with chronic stroke. Further research is required to investigate whether chiropractic spinal adjustment increases dorsiflexor muscle strength and walking function in people with stroke.